Thermo-Hydro-Mechanical Coupling Numerical Simulation on Mechanical Heterogeneity of Coal Rock. (9th August 2022) - Hu, Shuiqing; Wang, Daobing; Li, Yipeng; Liu, Xiongfei; Zhou, Fujian; Wang, Meng; He, Chunming; Yu, Bo
Abstract : Coal rock is a porous medium composed of organic matter and inorganic minerals, and it is very complex and highly heterogeneous. Coal bed methane (CBM) production is a thermo-hydro-mechanical (THM) coupling process in heterogeneous coal rock. THM coupling numerical simulation on the coal rock by considering the effect of mechanical heterogeneity is rarely reported. We use Weibull's probability density distribution function to characterize the heterogeneity in elastic modulus of the coal rock, establish a THM coupling 3D finite element model of the coal rock by considering the variation in pore pressure caused by methane desorption, the linear thermal expansion effect, and coal rock skeleton shrinkage and deformation, and analyze variation in permeability, porosity, stress, temperature, and pore pressure within the coal rock representative elementary volume (REV) of variable mechanical heterogeneity with the cross-coupling correlation between permeability and porosity, and thermal field, stress field, and pressure field. The results show that the evolution of porosity and permeability in the coal rock is a THM coupling process related to mechanical heterogeneity, thermal expansion effect, pore pressure change caused by CBM desorption, and stressed deformation in the coal rock skeleton. The permeability and porosity fluctuate within the heterogeneous coal rock. The permeability and porosity fluctuate more frequently in the coal rock with stronger mechanical heterogeneity. The mechanical heterogeneity promotes local stress concentration. The time for variation in the stress through the whole the coal rock REV and the value of the first principal stress increase when the coal rock heterogeneity is enhanced. Under the THM coupling effect, the strong heterogeneity of the coal rock causes fluctuation in the thermal field. The evolution of coal porosity and permeability is a THM coupling process. This study provides theoretical guidance for CBM exploitation.